2004
DOI: 10.1038/sj.bjc.6602198
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cycles of intermittent chemotherapy in metastatic androgen-independent prostate cancer

Abstract: Recently, completed phase III studies demonstrated a survival benefit for a fixed number of cycles of docetaxel-containing chemotherapy treatment of androgen-independent prostate cancer (AIPC). Management of patients who respond well to initial chemotherapy for AIPC remains ill-defined. We previously reported that in a select group of such patients, retreatment with the same regimen was feasible and was associated with quality of life gains. Here, we report that multiple cycles of such intermittent chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 6 publications
0
28
1
1
Order By: Relevance
“…This finding suggests that disease control was comparable between the intermittent tri-weekly DTX with BCL schedule and the continuous regimen. However, the median OS was significantly shorter than that reported by Beer 20 (20 months vs. 41 months), who used intermittent weekly DTX plus high-dose calcitriol. This difference may have been due to different patient characteristics and different regimens; however, the median survival in our study was similar to a report by Soga,35 who used tri-weekly DTX plus estramustine (20 months vs. 21 months).…”
Section: Intermittent Docetaxel For Prostate Cancer Yf LI Et Al 776contrasting
confidence: 41%
See 3 more Smart Citations
“…This finding suggests that disease control was comparable between the intermittent tri-weekly DTX with BCL schedule and the continuous regimen. However, the median OS was significantly shorter than that reported by Beer 20 (20 months vs. 41 months), who used intermittent weekly DTX plus high-dose calcitriol. This difference may have been due to different patient characteristics and different regimens; however, the median survival in our study was similar to a report by Soga,35 who used tri-weekly DTX plus estramustine (20 months vs. 21 months).…”
Section: Intermittent Docetaxel For Prostate Cancer Yf LI Et Al 776contrasting
confidence: 41%
“…The first two trials reported median times of 4 and 4.5 months. 9,20 The third study reported a median time of 2.8 months. 21 We believe that the first DTX holiday in the three trials and the present study differed for the following reasons.…”
Section: Intermittent Docetaxel For Prostate Cancer Yf LI Et Al 776mentioning
confidence: 99%
See 2 more Smart Citations
“…Second, from a clinical perspective, breaks in therapy or "drug holidays" may improve the quality of life for patients, allowing them to recover from the cumulative toxicity of chemotherapy during these "drug holidays." Resolution of drug side effects may also allow taxane therapy to be prolonged, given evidence of clinical efficacy, which could also improve outcomes (31,32).…”
Section: Strategies For Overcoming Taxane Resistancementioning
confidence: 99%